AUTONOMY OF HIGHER EDUCATION IN THE EUROPEAN UNION: Case C-66/18 European Commission v. Hungary - Dragišić, Radmila (Politeia, 2021)
Aware of the fact that autonomy is an important prerequisite for educational institutions to be able to perform their tasks, in this paper we explore and analyze one of the most interesting cases from the jurisprudence of the Court of Justice of the European Union in this area. Namely, the European Commission initiated proceedings against the Republic of Hungary for violating the rights of the European Union. The focus is on the Law on Higher Education of that member state, which has caused sharp controversies within the academic community in the countries of the European Economic Area, but also in third countries. Although the work is mostly dedicated to the free movement of services in the field of higher education, we inevitably explore the relationship between European Union law and legal instruments of the World Trade Organization (WTO), as well as the views of the Court of Justice regarding their interpretation. The case we are discussing is also important for the status of countries aspiring to become members of the European organization, since the European Parliament adopted a recommendation to include in the Copenhagen criteria for accession the defense and protection of academic freedom and institutional autonomy in order to prevent their endangerment in member states.
Keywords: University education; EU; jurisprudence of the EU Court of Justice; WTO; autonomy